Evaluation the Effect of Addition of Plasma Treated Polypropylene Fiber and Silanized Silicon Dioxide Nanoparticles Composite on Some Properties of Heat-Polymerized Polymethylmethacrylate - Ahmed Gh Ahmed; Intisar J Ismail (College of Dentistry/ University of Baghdad, 2016)
Background: Polymethylmethacrylate (PMMA) is the most ‎commonly used m‏aterial in denture construction. This material is ‎far from ideal in fulfilling the‎ mechanical requirements, like low impact and transverse strength and poor thermal conductivity are present in this material. The purpose of this study was to study the effect of addition a composite which include 1%wt silanized silicone dioxide nano fillers (SiO2) and 1wt% oxygen plasma treated polypropylene fiber (PP) on some properties of heat cured acrylic resin denture base material (PMMA). Materials and methods: One hund‏red (100) prepared specimens were divided into five groups according to the tests, each group consisted of 20 specimens and these were subdivided into two groups (unreinforced heat cured acrylic resin as control group)and reinforced acrylic resin with ( 1%wt Nano SiO2 and 1% wt oxygen plasma treated polypropylene ‎fibers) ‎group. The transverse strength¸ impact ‎strength, indentation hardness (shoreD), surface roughness and water sorption and solubility were investigated. The results were statistically analyzed using descriptive and t-test. Results: The results of this study show that a highly significant increase in impact strength (10.4939 Kj/m2),surface hardness (89.9375) surface roughness (0.9498) and water sorption (0.0171mg/cm2) was observed with the addition of 1%wt silanized (SiO2) nanoparticles and 1%wt oxygen plasma treated polypropylene fibers to (PMMA) , also significant decrease in transverse strength (103.4753 N/mm2), nonsignificant decrease occurred in water solubility which was (0.0005mg/cm2). Conclusion: The incorporation of 1%wt silanized SiO2 nanoparticles and 1%wt oxygen plasma treated polypropylene fiber to heat cure PMMA form a composite improves the impact strength, surface hardness and surface roughness of acrylic resin, at the same time this addition increase the water sorption and decrease water solubility; while significant decrease in transverse strength.